2006
DOI: 10.1253/circj.70.1457
|View full text |Cite
|
Sign up to set email alerts
|

Critical Level of Cerebral Oxygenation During Exercise in Patients With Left Ventricular Dysfunction

Abstract: erebral blood flow in the resting state is regulated adequately by complex compensatory mechanisms. 1,2 During exercise, however, the O2 demand of exercising muscles surges to levels 10-15-fold higher than that in the resting state. The blood flow to the exercising muscles increases tremendously to meet this sudden surge in O2 demand. As the blood flow to each organ is determined by cardiac output, an increased distribution of blood flow to the muscle may deprive other organs of blood, especially in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…3 We recently compared the decreased levels of O2Hb and TOI at the forehead during exercise in patients with LV dysfunction with those in subjects who had experienced reduced consciousness because of a sudden drop in blood pressure induced by a parasympathetic reflex or sustained ventricular tachycardia. 22 We found that the decreases in these indexes during exercise in some patients were comparable to those in subjects who experienced reduced consciousness, which suggests that the indexes of cerebral oxygenation may drop to levels low enough to affect the level of consciousness during maximal exercise in patients with severe LV dysfunction. 22 Based on these findings, we hypothesized that breathing high O2 would raise the PaO2 and subsequently improve cerebral oxygenation in patients with LV dysfunction.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…3 We recently compared the decreased levels of O2Hb and TOI at the forehead during exercise in patients with LV dysfunction with those in subjects who had experienced reduced consciousness because of a sudden drop in blood pressure induced by a parasympathetic reflex or sustained ventricular tachycardia. 22 We found that the decreases in these indexes during exercise in some patients were comparable to those in subjects who experienced reduced consciousness, which suggests that the indexes of cerebral oxygenation may drop to levels low enough to affect the level of consciousness during maximal exercise in patients with severe LV dysfunction. 22 Based on these findings, we hypothesized that breathing high O2 would raise the PaO2 and subsequently improve cerebral oxygenation in patients with LV dysfunction.…”
Section: Discussionmentioning
confidence: 53%
“…22 We found that the decreases in these indexes during exercise in some patients were comparable to those in subjects who experienced reduced consciousness, which suggests that the indexes of cerebral oxygenation may drop to levels low enough to affect the level of consciousness during maximal exercise in patients with severe LV dysfunction. 22 Based on these findings, we hypothesized that breathing high O2 would raise the PaO2 and subsequently improve cerebral oxygenation in patients with LV dysfunction. As expected, in the present study we found that breathing 50% O2 diminished the decrease in cerebral O2Hb in patients with reduced LVEF who had clearly demonstrated it during moderate to high intensity exercise while breathing room air.…”
Section: Discussionmentioning
confidence: 53%
“…19 We found that the decreases in cerebral O2Hb during exercise in some patients were comparable to those in subjects who experienced reduced consciousness. This finding suggests that the index of cerebral oxygenation might drop to levels low enough during maximal exercise to affect the level of consciousness in some cardiac patients, especially those with severe left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 56%
“…From the results of the previous investigations, 1,2,7,19 we assumed that the decrease in O2Hb during exercise would be an abnormal phenomenon. Thus, we used the ΔO2Hb level of "0" as a cut-off point for the Kaplan -Meier method without using a receiver operating characteristics (ROC) curve analysis.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Considering the potential clinical relevance of their findings, 1 we would suggest they expand the results to include the TOI data as correctly done in their other recent interesting clinical studies. 10,11 …”
Section: To the Editormentioning
confidence: 99%